Halal guarantee institutions and systems around the world - Nurjannah Nurjannah; Syahruddin Kadir; Ahmad Zuhry Amir; Mifrah Nurbadri Ramadani; Muh. Faisal (Nur Science Institute, 2025)
Halal certification is a process that involves several stages to obtain a halal certificate and demonstrate that the ingredients, production process, and halal assurance system meet the standards of the Halal Assessment and Certification Institute. The purpose of this study is to look at halal assurance mechanisms in various worlds. This research is library research with a descriptive qualitative method. Data obtained from secondary data, namely, various journals, research, and books relevant to the discussion. The data obtained from various literature sources are then analysed, data reduction is performed, and the resulting data are classified. The results of this study indicate that in various parts of the world, there are many halal certification bodies whose job is to guarantee the halal status of products circulating in their countries and those exported to other countries. For example, Malaysia with JAKIM, Thailand with CICOT, Japan with the Japan Muslim Association (JMA), the Netherlands with the Halal Feed and Food Inspection Authority (HFFIA), and America with the Islamic Food and Nutrition Council of America (IFANCA).